2020
DOI: 10.1186/s42836-020-00043-7
|View full text |Cite
|
Sign up to set email alerts
|

CRP (C Reactive Protein) level after total knee replacement in Indian population--- does it follow Anglo-Saxon trend?

Abstract: Background: This study was to determine how C-reactive protein (CRP) responds after total knee replacement (TKR), including both unilateral and simultaneous bilateral TKR in Indian population and if it follows Anglo-Saxon trend. Published literature from North America and Europe shows CRP value peaks on the 2nd post-operative day and drops to normal by 6-8 weeks. We started the study with null hypothesis. Material and methods: This is a prospective study, with 50 patients (all females, 25 received unilateral o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…In a study by Park et al 13 temporal values of CRP after TKR reached the normal reference at the end of 6th week. In another study by Londhe et al 14 , CRP levels after unilateral TKR reached the normal baseline level after 12 weeks and at the end of 16 weeks after bilateral TKR. In an analysis done on the Iranian population by Nazem et al 15 , CRP levels after TKR and THR did not reach the normal baseline values even after one year of the procedure.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In a study by Park et al 13 temporal values of CRP after TKR reached the normal reference at the end of 6th week. In another study by Londhe et al 14 , CRP levels after unilateral TKR reached the normal baseline level after 12 weeks and at the end of 16 weeks after bilateral TKR. In an analysis done on the Iranian population by Nazem et al 15 , CRP levels after TKR and THR did not reach the normal baseline values even after one year of the procedure.…”
Section: Discussionmentioning
confidence: 86%
“…Though there are numerous studies in the literature evaluating CRP and ESR trends post total hip and knee replacement surgeries, very few have actually evaluated the effect of the racial factors affecting CRP values 18 . Most of the studies have primarily been done on a subset of the european population 9 - 13 and to the best of the author's knowledge, very few have studied the early post-operative trend of CRP and ESR on a subset of Asian population 14 , 15 . The present study is an attempt to fill this gap in literature by evaluating the CRP and ESR trend in an Indian population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, all 105 patients were in antibiotic coverage which might have influenced the response of inflammatory markers, hence similar results were not obtained. Londhe et al [ 18 ] concluded that in the Indian TKR patients, the CRP values take longer time to return to normal than in their Anglo-Saxon counterparts. Due to the variable nature of raised CRP, marginal elevations in CRP can be difficult to interpret and should not be utilized as an isolated test for the clinical picture.…”
Section: Discussionmentioning
confidence: 99%
“…H/o, history of; NLR, neutrophil-to-lymphocyte ratio; ANOVA, analysis of variance; COPD, chronic obstructive pulmonary disease; SD, standard deviation; TIA, transient ischemic attack results were not obtained. Londhe et al [18] concluded that in the Indian TKR patients, the CRP values take longer time to return to normal than in their Anglo-Saxon counterparts. Due to the variable nature of raised CRP, marginal elevations in CRP can be difficult to interpret and should not be utilized as an isolated test for the clinical picture.…”
Section: Sn Transfusion Requirementmentioning
confidence: 99%